2013
DOI: 10.1016/j.addbeh.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive attributions for smoking in subsequent smoking progression and regression among adolescents in China

Abstract: Previous studies have documented that cognitive attributions are correlated with adolescent smoking. The present study further explored whether cognitive attributions for smoking influenced adolescents’ future smoking behaviors, especially transitions to more advanced stages of smoking. Participants were 12,382 middle and high school students (48.5% males and 51.5% females) in seven large cities in China. They completed two waves of surveys one year apart. Cognitive attributions for smoking and three smoking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…This is consistent with other studies (Spelman, 2007;Guo, 2008) that found adverse transitions to be higher among male adolescents. However, there are also studies that found a greater risk of adverse transitions among females (Richmond, 1999;Lloyd-Richardson et al, 2002).…”
supporting
confidence: 83%
“…This is consistent with other studies (Spelman, 2007;Guo, 2008) that found adverse transitions to be higher among male adolescents. However, there are also studies that found a greater risk of adverse transitions among females (Richmond, 1999;Lloyd-Richardson et al, 2002).…”
supporting
confidence: 83%
“…In both this original study and a more recent international study (Guo, Unger, Palmer, Chou, & Johnson, 2013), curiosity about smoking was associated with receptivity to tobacco industry marketing messages, suggesting that it could be a mediator variable through which marketing influences initiation.…”
Section: Introductionmentioning
confidence: 71%
“…Building curiosity is a focus for many educational endeavors (Day, 1982; Simon, 2001), as well as the target for marketers promoting experimentation with their particular consumer behavior (Smith & Swinyard, 1988). As such, multiple studies have reported that the majority of smokers, when asked to reflect on why they started to smoke, cite curiosity about smoking (Cronan, Conway, & Kaszas, 1991; Guo et al, 2013). In this study, as in previous studies, pre-teens who were receptive to tobacco industry marketing messages that are known to encourage smoking, were also likely to develop curiosity cognitions.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Efforts to further refine identification of the lowest risk teens suggested inquiring about cognitions that may precede formation of intentions about smoking. When current smokers are asked for reasons they initiated smoking, most report that they were motivated by curiosity, 12,13 as people are similarly motivated for many new behaviors. 14 Curiosity has long been considered a primary cognitive motivational state underlying pursuit of novel experiences.…”
Section: Introductionmentioning
confidence: 99%